High-strength wear-resistant aluminum-magnesium-silicon series aluminum alloy and preparation method thereof

By adding carbon nanotubes and zirconium elements to aluminum-magnesium-silicon aluminum alloys, combined with specific chemical composition ratios and preparation process steps, the problem of insufficient strength and wear resistance of existing aluminum alloys is solved, and the improvement of high strength, wear resistance and corrosion resistance is achieved, while reducing production costs.

CN119843114APending Publication Date: 2025-04-18CHIZHOU JIUHUA MINGKUN ALUMINUM IND

Patent Information

Application Number
CN202411893838.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The strength and wear resistance of existing aluminum-magnesium-silicon aluminum alloys are difficult to meet high performance requirements, and the addition of a variety of rare earth metal combinations leads to complex control of raw material components and high cost.

Method used

By adding carbon nanotubes and zirconium elements to the aluminum alloy, combining specific chemical composition ratios and preparation process steps, the strength and wear resistance of the alloy are improved, cost-effective and simplified raw material formulation.

Benefits of technology

It significantly improves the mechanical strength, wear resistance and corrosion resistance of aluminum alloys, reduces production costs, simplifies raw material formulation, and meets high-performance needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201240220000121
    Figure BDA0005201240220000121
Patent Text Reader

Abstract

The invention discloses a high-strength wear-resistant aluminum-magnesium-silicon series aluminum alloy and a preparation method thereof, and belongs to the technical field of aluminum alloy materials, and the aluminum-magnesium-silicon series aluminum alloy comprises the following chemical components in percentage by mass: 1.0-1.8% of Si, 0.8-1.2% of Mg, 0.1-0.3% of carbon nanotubes, 0.2-0.3% of Zr, less than 0.1% of other inevitable impurity elements, and the balance of Al. The preparation method comprises the steps of melting, refining, casting, extruding and the like. According to the aluminum alloy, the wear resistance and corrosion resistance of the material are improved through the synergistic effect of silicon, magnesium, carbon nanotubes, zirconium and aluminum, the aluminum alloy has high strength and hardness, chemical components in the alloy are simple, the cost can be reduced, and technological operation can be simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy materials, and specifically relates to a high-strength wear-resistant aluminum-magnesium-silicon alloy and a preparation method thereof. Background Art

[0002] As a lightweight metal structural material, aluminum alloy has the characteristics of low density, good corrosion resistance, high specific strength, and excellent forming process. It is widely used in equipment manufacturing fields such as aircraft, launch vehicles, new energy vehicles, ships, and chemicals. Among the aluminum alloy series, the aluminum-magnesium-silicon alloy series has medium strength, good strength and corrosion resistance. It has good welding performance and process performance, and excellent oxidation coloring performance. It is often used in the manufacture of transportation parts, such as luggage racks, doors and windows, and car bodies of cars, as well as the housings of electronic equipment.

[0003] In order to improve the fuel economy of automobiles, their structures are gradually developing towards lightweight. Many automobile parts need to be replaced with lightweight materials. The density of aluminum-magnesium-silicon aluminum alloys is significantly lower than that of traditional cast iron materials. They also have good processing performance, thermal conductivity and corrosion resistance, and can be used as replacement materials. However, in actual applications, some automobile parts need to have higher strength and wear resistance, such as engine blocks, automobile bumpers and brake discs. The strength and wear resistance of aluminum-magnesium-silicon aluminum alloys prepared by existing technologies are difficult to meet the requirements of high performance. The improvement of their strength and wear resistance is of great significance to promoting the lightweighting of automobiles.

[0004] In order to improve the strength and wear resistance of aluminum-magnesium-silicon alloys, manufacturers often add other elements to the alloy for doping modification. The patent with publication number CN107974586A discloses a wear-resistant aluminum alloy, whose alloy composition includes by mass percentage: silicon 8% to 12%, copper 1.5% to 3.5%, magnesium 2% to 4%, zinc 0.5% to 0.7%, boron 0.2% to 1%, iron 0.5% to 1.2%, titanium 0.1% to 0.5%, manganese 0.4% to 0.8%, antimony 0.5% to 1%, osmium 0.2% to 0.38%, iridium 0.15% to 0.25%, and the balance is aluminum and impurities. The patent increases the strength by adding copper to the raw materials, and improves the mechanical properties of the aluminum alloy by adding antimony, osmium and iridium in combination, thereby improving the hardness, wear resistance and corrosion resistance of the aluminum alloy. From the perspective of raw materials, while copper is added to the aluminum alloy to improve the strength, multiple metals such as antimony, osmium and iridium need to be added to compensate for the loss of corrosion resistance. The wide variety of materials makes the operation of controlling the raw material components complicated, the cost burden is high, and it is not conducive to the actual production of materials.

[0005] When adding other metal materials to modify and improve performance, it is necessary to consider the negative effects they bring. The comprehensive performance of the alloy material must meet the product requirements. Therefore, on the basis of improving strength and wear resistance, the additional cost pressure and complexity of the raw material process must be reduced. This problem is urgently needed to be solved in the current optimization of alloy material formulas. Summary of the invention

[0006] The purpose of the present invention is to provide a high-strength wear-resistant aluminum-magnesium-silicon aluminum alloy and a preparation method thereof, so as to improve the strength and wear resistance of the alloy material, avoid a substantial increase in cost, and simplify the raw material formula.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] The present invention provides a high-strength wear-resistant aluminum-magnesium-silicon aluminum alloy, which comprises the following chemical components by mass percentage:

[0009] Si: 1.0-1.8%, Mg: 0.8-1.2%, carbon nanotubes: 0.1-0.3%, Zr: 0.2-0.3%, the content of other inevitable impurity elements is less than 0.1%, and the balance is Al.

[0010] On the basis of aluminum, magnesium and silicon, carbon nanotubes and zirconium are added. Compared with the combination of other rare earth metals, the cost of carbon nanotubes and zirconium is lower, and the synergistic effect of the two can promote the comprehensive improvement of the wear resistance, mechanical strength and corrosion resistance of aluminum alloy materials.

[0011] Furthermore, the wall thickness of the carbon nanotube is 5-10 nm.

[0012] Carbon nanotubes have the inherent properties of carbon materials, the thermal conductivity of metal materials, the heat resistance and corrosion resistance of ceramic materials, the weavability of textile fibers, and the lightness and easy processing of polymer materials. The mechanical properties of carbon nanotubes and their small diameter and large aspect ratio will bring better reinforcement effects. Their staggered position in the material can hinder the precipitation and precipitation of small particles, and enhance the toughness and strength of the material. The wall thickness of carbon nanotubes is an important parameter, which affects the mechanical properties of carbon nanotubes. Single-walled carbon nanotubes have a single layer of carbon atoms and a very thin wall thickness of about 0.1-2nm. In contrast, multi-walled carbon nanotubes have multiple layers of carbon atoms and a wall thickness of several nanometers to tens of nanometers. Multi-walled carbon nanotubes are more stable than single-walled carbon nanotubes and can provide better mechanical strength and thermal stability. Due to the existence of an interface layer between carbon nanotubes and the alloy substrate, excessive wall thickness will reduce the stress transfer effect between carbon nanotubes and the substrate, thereby affecting the overall strength and thermal conductivity.

[0013] Furthermore, the mass ratio of the carbon nanotubes to Zr is 1-3:2.

[0014] Furthermore, the mass ratio of Si to Mg is 10-13:8.

[0015] In aluminum alloys, the ratio of silicon to magnesium is usually 1:1.73, which is based on the formation of Mg in the alloy. 2 In the present invention, under the action of added carbon nanotubes and zirconium, silicon and magnesium will form a hybrid phase with other elements, and the ratio of silicon and magnesium needs to be adjusted based on the overall performance of the material to ensure that the role of each element is fully exerted.

[0016] The present invention also provides a method for preparing a high-strength wear-resistant aluminum-magnesium-silicon alloy, comprising the following steps:

[0017] Step 1: prepare metal raw materials according to mass percentage, heat aluminum to 740-780°C to melt, raise the temperature to 1000-1500°C after it is completely melted, add zirconium and carbon nanotubes, stir and mix them for melting;

[0018] Step 2: Cool down to 800-900°C, add silicon, and stir the metal solution until it is completely melted;

[0019] Step 3: Cool down to 700-750°C, add magnesium, and stir until the magnesium is completely melted;

[0020] Step 4: Degas and deslag the molten metal to remove oxygen, hydrogen and other harmful gases and remove slag;

[0021] Step 5: Add refining agent into the molten metal for heat preservation and refining at a refining temperature of 720-740°C;

[0022] Step 6: After refining, casting is carried out, and the ingot is subjected to homogenization annealing, peeling, hot extrusion forming and solution quenching treatment.

[0023] During the preparation process, zirconium and carbon nanotubes, which account for a smaller proportion, are added first. Zirconium and carbon nanotubes have better thermal stability. Under high temperature conditions, the molten aluminum metal liquid has better fluidity and is more evenly mixed with zirconium and carbon nanotubes. Silicon and magnesium are then added in sequence. Silicon has a higher melting point. Adding silicon first can make it easier to melt and evenly distribute in the aluminum. Magnesium has a lower melting point. If magnesium is added when silicon is not completely melted, it may cause oxidation or uneven distribution of magnesium. The solid solubility of magnesium in aluminum is low. Adding magnesium after silicon is completely dissolved can avoid magnesium segregation.

[0024] Furthermore, the cooling rate in step 2 is 5-10°C / min, and the cooling rate in step 3 is 3-5°C / min.

[0025] During the melting process, accelerating the cooling rate can achieve rapid melting and reduce the impact of oxygen intrusion on the material composition, but too fast cooling will lead to uneven temperature inside the molten metal and uneven distribution of internal components.

[0026] Furthermore, the degassing is to introduce nitrogen into the molten metal to take hydrogen and impurities out of the molten metal, and the degassing efficiency is high.

[0027] Furthermore, the refining agent is one of hexachloroethane, sodium chloride and potassium chloride, and the mass proportion of the refining agent in the molten metal is 0.05%-0.1%.

[0028] Through the comprehensive degassing and impurity removal of nitrogen and solid refining agents, the purity of the molten metal can be efficiently improved, thereby improving the performance and quality of the aluminum alloy.

[0029] Furthermore, the temperature of the homogenization annealing is 560-600°C, and the temperature is kept for 6-8 hours before cooling to room temperature. Homogenization annealing promotes atomic diffusion by increasing the temperature, so that the alloy composition and microstructure reach a uniform state.

[0030] Further, the solution quenching is set as follows:

[0031] The solution temperature is 540-560℃, and water quenching is carried out after keeping warm for 2-3h. The artificial aging temperature is 160-180℃, and it lasts for 8-10h.

[0032] In the solution stage, the aluminum alloy is heated to a high temperature so that the solute elements in the alloy dissolve into the solid solution to form a supersaturated solid solution. This helps to homogenize the microstructure of the alloy and improve its mechanical properties. After the solution treatment, the material is cooled and artificially aged. The solute elements in the alloy precipitate to form fine precipitates, thereby enhancing the strength and hardness of the material.

[0033] Beneficial effects of the present invention:

[0034] (1) The addition of carbon nanotubes to the aluminum matrix composite significantly improves its strength and elastic modulus. Mg has a higher oxygen affinity than Al, which makes it easier for Mg to segregate around carbon nanotubes in the composite to form oxides. 2 O 4 The formation of phase can effectively improve the interface bonding of the composite material. The Mg element destroys the natural Al 2 O 3 layer, promoting the full dissolution of Mg element into the α-Al matrix, increasing the supersaturated solid solubility, and making the strengthening phase MgSi more evenly distributed in the matrix.

[0035] (2) Adding zirconium to aluminum alloy, zirconium and aluminum form ZrAl 3Compounds can hinder the recrystallization process, refine the recrystallized grains, and due to ZrAl 3 The formation of the phase leads to an increase in the effective core number of the metastable β phase, avoiding the formation of coarse β phase, and the alloy has higher strength and hardness.

[0036] (3) Under high temperature conditions, zirconium and carbon will form a stable carbide ZrC, which has excellent corrosion resistance, high hardness and high strength, and can improve the wear resistance of the material. In the aluminum matrix, the solid solubility of ZrC is relatively small, and it will precipitate at the interface during the aging treatment. The addition of low content of zirconium and carbon will limit the grain size of the precipitated phase. The ZrC precipitated at the aluminum alloy interface is small in size, forming a particle layer with higher hardness on the surface of the aluminum alloy.

[0037] (4) In order to enhance the wear resistance of the alloy, the silicon content in the present invention is relatively high, and the increase in silicon content will lead to a relatively large size of Si particles formed in the alloy, which is prone to stress concentration when bearing, and the material strength of the alloy is reduced. By adding carbon nanotubes, SiC will be formed at high temperatures due to the presence of high concentration of silicon at the interface, so that the excess silicon in the alloy is more dispersed, the generation of coarse Si phase is suppressed, the ratio of carbon nanotubes and zirconium in the alloy is controlled, and the formed SiC and ZrC can be combined to form a continuous wear-resistant layer, and oxygen can be prevented from diffusing into the interior of the alloy, thereby improving the wear resistance and corrosion resistance of the material. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] This embodiment provides a high-strength wear-resistant aluminum-magnesium-silicon aluminum alloy, which includes the following chemical components by mass percentage:

[0041] Si: 1.0%, Mg: 0.8%, carbon nanotubes (wall thickness 5-10nm): 0.1%, Zr: 0.2%, the content of other inevitable impurity elements is less than 0.1%, and the balance is Al.

[0042] The preparation steps are as follows:

[0043] Step 1: prepare metal raw materials according to the above mass percentages, heat aluminum to 780°C to melt, raise the temperature to 1300°C after it is completely melted, add zirconium and carbon nanotubes, stir and mix, and melt;

[0044] Step 2: Cool down to 800°C, set the cooling rate to 10°C / min, add silicon, and stir the metal solution until it is completely melted;

[0045] Step 3: Cool down to 700°C, set the cooling rate to 5°C / min, add magnesium, and stir until the magnesium is completely melted;

[0046] Step 4: Introduce nitrogen into the molten metal to degas and deslag the molten metal, remove oxygen, hydrogen and other harmful gases, and remove scum;

[0047] Step 5: adding hexachloroethane into the molten metal for heat preservation and refining, wherein the mass proportion of hexachloroethane in the molten metal is 0.1% and the refining temperature is 740°C;

[0048] Step 6: After refining, casting is performed, and the ingot is homogenized and annealed. The homogenization annealing temperature is set to 560°C, and it is kept warm for 8 hours before cooling to room temperature. After the casting is peeled, the workpiece is hot extruded to obtain the workpiece, and the workpiece is solution quenched. The solution temperature is set to 540°C, and it is kept warm for 2 hours before water quenching. The artificial aging temperature is 180°C for 8 hours.

[0049] Example 2

[0050] The only difference from Example 1 is that the mass percentage of Si is adjusted to 1.2%, and the other conditions and steps are the same as Example 1.

[0051] Example 3

[0052] The only difference from Example 1 is that the mass percentage of Si is adjusted to 1.3%, and the other conditions and steps are the same as Example 1.

[0053] Example 4

[0054] The only difference from Example 1 is that the mass percentage of Si is adjusted to 1.5%, the mass percentage of Mg is adjusted to 1.0%, and the mass percentages of other chemical components are the same as in Example 1. The specific preparation steps are as follows:

[0055] Step 1: prepare metal raw materials according to the above mass percentages, heat aluminum to 750°C to melt, raise the temperature to 1300°C after it is completely melted, add zirconium and carbon nanotubes, stir and mix, and melt;

[0056] Step 2: Cool down to 850°C, set the cooling rate to 10°C / min, add silicon, and stir the metal solution until it is completely melted;

[0057] Step 3: Cool down to 730°C, set the cooling rate to 4°C / min, add magnesium, and stir until the magnesium is completely melted;

[0058] Step 4: Introduce nitrogen into the molten metal to degas and deslag the molten metal, remove oxygen, hydrogen and other harmful gases, and remove scum;

[0059] Step 5: Add sodium chloride to the molten metal for heat preservation and refining, the mass proportion of hexachloroethane in the molten metal is 0.05%, and the refining temperature is 730°C;

[0060] Step 6: After refining, casting is performed, and the ingot is homogenized and annealed. The homogenization annealing temperature is set to 580°C, and it is kept warm for 7 hours before cooling to room temperature. After the casting is peeled, the workpiece is hot extruded to obtain the workpiece, and the workpiece is solution quenched. The solution temperature is set to 550°C, and it is kept warm for 2.5 hours before water quenching. The artificial aging temperature is 170°C for 9 hours.

[0061] Example 5

[0062] The only difference from Example 1 is that the mass percentage of Si is adjusted to 1.8%, the mass percentage of Mg is adjusted to 1.2%, and the mass percentages of other chemical components are the same as in Example 1. The specific preparation steps are as follows:

[0063] Step 1: prepare metal raw materials according to the above mass percentages, heat aluminum to 740°C to melt, raise the temperature to 1300°C after it is completely melted, add zirconium and carbon nanotubes, stir and mix, and melt;

[0064] Step 2: Cool down to 900°C, set the cooling rate to 10°C / min, add silicon, and stir the metal solution until it is completely melted;

[0065] Step 3: Cool down to 750°C, set the cooling rate to 3°C / min, add magnesium, and stir until the magnesium is completely melted;

[0066] Step 4: Introduce nitrogen into the molten metal to degas and deslag the molten metal, remove oxygen, hydrogen and other harmful gases, and remove scum;

[0067] Step 5: Add sodium chloride to the molten metal for heat preservation and refining, the mass proportion of hexachloroethane in the molten metal is 0.05%, and the refining temperature is 730°C;

[0068] Step 6: After refining, casting is performed, and the ingot is homogenized and annealed. The homogenization annealing temperature is set to 580°C, and it is kept warm for 7 hours before cooling to room temperature. After the casting is peeled, the workpiece is hot extruded to obtain the workpiece, and the workpiece is solution quenched. The solution temperature is set to 550°C, and it is kept warm for 2.5 hours before water quenching. The artificial aging temperature is 170°C for 9 hours.

[0069] Example 6

[0070] The only difference from Example 4 is that the mass percentage of carbon nanotubes is adjusted to 0.2%, and the mass percentages of other chemical components are the same as in Example 4. The specific preparation steps are as follows:

[0071] Step 1: prepare metal raw materials according to the above mass percentages, heat aluminum to 750°C to melt, raise the temperature to 1400°C after it is completely melted, add zirconium and carbon nanotubes, stir and mix, and melt;

[0072] Step 2: Cool down to 900°C, set the cooling rate to 8°C / min, add silicon, and stir the metal solution until it is completely melted;

[0073] Step 3: Cool down to 750°C, set the cooling rate to 4°C / min, add magnesium, and stir until the magnesium is completely melted;

[0074] Step 4: Introduce nitrogen into the molten metal to degas and deslag the molten metal, remove oxygen, hydrogen and other harmful gases, and remove scum;

[0075] Step 5: Add sodium chloride to the molten metal for heat preservation and refining, the mass proportion of hexachloroethane in the molten metal is 0.05%, and the refining temperature is 730°C;

[0076] Step 6: After refining, casting is performed, and the ingot is homogenized and annealed. The homogenization annealing temperature is set to 600°C, and it is kept warm for 6 hours before cooling to room temperature. After the casting is peeled, the workpiece is hot extruded to obtain the workpiece, and the workpiece is solution quenched. The solution temperature is set to 550°C, and it is kept warm for 2.5 hours before water quenching. The artificial aging temperature is 170°C for 9 hours.

[0077] Example 7

[0078] The only difference from Example 4 is that the mass percentage of carbon nanotubes is adjusted to 0.3%, and the mass percentages of other chemical components are the same as in Example 4. The specific preparation steps are as follows:

[0079] Step 1: prepare metal raw materials according to the above mass percentages, heat aluminum to 750°C to melt, raise the temperature to 1400°C after it is completely melted, add zirconium and carbon nanotubes, stir and mix, and melt;

[0080] Step 2: Cool down to 900°C, set the cooling rate to 8°C / min, add silicon, and stir the metal solution until it is completely melted;

[0081] Step 3: Cool down to 750°C, set the cooling rate to 4°C / min, add magnesium, and stir until the magnesium is completely melted;

[0082] Step 4: Introduce nitrogen into the molten metal to degas and deslag the molten metal, remove oxygen, hydrogen and other harmful gases, and remove scum;

[0083] Step 5: Add sodium chloride to the molten metal for heat preservation and refining, the mass proportion of hexachloroethane in the molten metal is 0.05%, and the refining temperature is 730°C;

[0084] Step 6: After refining, casting is performed, and the ingot is homogenized and annealed. The homogenization annealing temperature is set to 600°C, and it is kept warm for 6 hours before cooling to room temperature. After the casting is peeled, the workpiece is hot extruded to obtain the workpiece, and the workpiece is solution quenched. The solution temperature is set to 560°C, and it is water quenched after being kept warm for 3 hours. The artificial aging temperature is 160°C for 10 hours.

[0085] Example 8

[0086] The only difference from Example 4 is that the mass percentage of carbon nanotubes is adjusted to 0.25%, the mass percentage of Zr is adjusted to 0.25%, and the mass percentages of other chemical components are the same as in Example 4. The specific preparation steps are as follows:

[0087] Step 1: prepare metal raw materials according to the above mass percentages, heat aluminum to 740°C to melt, raise the temperature to 1500°C after it is completely melted, add zirconium and carbon nanotubes, stir and mix, and melt;

[0088] Step 2: Cool down to 900°C, set the cooling rate to 8°C / min, add silicon, and stir the metal solution until it is completely melted;

[0089] Step 3: Cool down to 750°C, set the cooling rate to 4°C / min, add magnesium, and stir until the magnesium is completely melted;

[0090] Step 4: Introduce nitrogen into the molten metal to degas and deslag the molten metal, remove oxygen, hydrogen and other harmful gases, and remove scum;

[0091] Step 5: Add sodium chloride to the molten metal for heat preservation and refining, the mass proportion of hexachloroethane in the molten metal is 0.05%, and the refining temperature is 730°C;

[0092] Step 6: After refining, casting is performed, and the ingot is homogenized and annealed. The homogenization annealing temperature is set to 600°C, and it is kept warm for 8 hours before cooling to room temperature. After the casting is peeled, the workpiece is hot extruded to obtain the workpiece, and the workpiece is solution quenched. The solution temperature is set to 560°C, and it is water quenched after being kept warm for 3 hours. The artificial aging temperature is 160°C for 10 hours.

[0093] Example 9

[0094] The only difference from Example 6 is that the mass percentage of carbon nanotubes is adjusted to 0.3%, the mass percentage of Zr is adjusted to 0.3%, and the mass percentages of other chemical components are the same as those in Example 4. The specific preparation steps are as follows:

[0095] Step 1: prepare metal raw materials according to the above mass percentages, heat aluminum to 740°C to melt, raise the temperature to 1500°C after it is completely melted, add zirconium and carbon nanotubes, stir and mix, and melt;

[0096] Step 2: Cool down to 900°C, set the cooling rate to 5°C / min, add silicon, and stir the metal solution until it is completely melted;

[0097] Step 3: Cool down to 750°C, set the cooling rate to 4°C / min, add magnesium, and stir until the magnesium is completely melted;

[0098] Step 4: Introduce nitrogen into the molten metal to degas and deslag the molten metal, remove oxygen, hydrogen and other harmful gases, and remove scum;

[0099] Step 5: Add sodium chloride into the molten metal for heat preservation and refining, the mass proportion of hexachloroethane in the molten metal is 0.05%, and the refining temperature is 720°C;

[0100] Step 6: After refining, casting is performed, and the ingot is homogenized and annealed. The homogenization annealing temperature is set to 600°C, and it is kept warm for 8 hours before cooling to room temperature. After the casting is peeled, the workpiece is hot extruded to obtain the workpiece, and the workpiece is solution quenched. The solution temperature is set to 560°C, and it is water quenched after being kept warm for 3 hours. The artificial aging temperature is 160°C for 10 hours.

[0101] Comparative Example 1

[0102] Compared with Example 1, the aluminum alloy material provided in this comparative example does not add carbon nanotubes, and uses Zr of equal mass to replace the carbon nanotubes. Other conditions and steps are the same as those in Example 1.

[0103] Comparative Example 2

[0104] Compared with Example 1, the aluminum alloy material provided in this comparative example does not add zirconium element, and uses carbon nanotubes of equal mass to replace Zr. Other conditions and steps are the same as those in Example 1.

[0105] Comparative Example 3

[0106] Compared with Example 1, the aluminum alloy material provided in this comparative example does not add carbon nanotubes and zirconium elements, and the mass percentages of other chemical components are the same as those in Example 1. The specific preparation steps are as follows:

[0107] Step 1: prepare the metal raw materials according to the above mass percentage, and heat the aluminum to 740°C to melt;

[0108] Step 2: Raise the temperature to 800°C, add silicon, and stir the metal solution until it is completely melted;

[0109] Step 3: Cool down to 700°C, set the cooling rate to 5°C / min, add magnesium, and stir until the magnesium is completely melted;

[0110] Step 4: Introduce nitrogen into the molten metal to degas and deslag the molten metal, remove oxygen, hydrogen and other harmful gases, and remove scum;

[0111] Step 5: adding hexachloroethane into the molten metal for heat preservation and refining, wherein the mass proportion of hexachloroethane in the molten metal is 0.1% and the refining temperature is 740°C;

[0112] Step 6: After refining, casting is performed, and the ingot is homogenized and annealed. The homogenization annealing temperature is set to 560°C, and it is kept warm for 8 hours before cooling to room temperature. After the casting is peeled, the workpiece is hot extruded to obtain the workpiece, and the workpiece is solution quenched. The solution temperature is set to 540°C, and it is kept warm for 2 hours before water quenching. The artificial aging temperature is 180°C for 8 hours.

[0113] The performance of the alloy materials prepared in Example 1 to Example 9 and Comparative Example 1 to Comparative Example 3 was tested, and the results are shown in Table 1.

[0114] Wear resistance test refers to GB / T 34501-2017 Hard Alloy Wear Test Method to test volume wear.

[0115] Mechanical strength testing refers to "GB / T 228.1-2021 Tensile test of metal materials Part 1: Room temperature test method" to test the tensile strength of the material.

[0116] The corrosion resistance test refers to HB5455 "Test method for exfoliation corrosion of aluminum alloy" to test the exfoliation corrosion level of the test material.

[0117] Table 1

[0118]

[0119] It can be seen from Table 1 that the various properties of the embodiment are much better than those of the comparative example. In Example 2, the silicon-magnesium ratio in the aluminum alloy material is appropriately increased, and the silicon content in the alloy is excessive, which helps to form a more uniform and fine Mg 2Si phase improves the overall performance of the material, but when the silicon-magnesium ratio is too large, excess silicon will form coarse silicon particles, weakening the strength of the material. The performance in Example 3 is significantly reduced. Example 4 further increases the proportion of the two in the material on the basis of the silicon-magnesium ratio in Example 2, and its strength and wear resistance are improved. In Examples 6 and 7, the increase in the proportion of carbon nanotubes and zirconium elements will promote the formation of SiC, which combines with ZrC to form a continuous wear-resistant layer, and the wear resistance of the material is significantly improved. In Examples 8 and 9, the content of carbon nanotubes and zirconium in the aluminum alloy material is gradually increased based on the mass ratio of 1:1, which has an excellent effect on enhancing the strength and hardness of the material.

[0120] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0121] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength wear-resistant aluminum-magnesium-silicon alloy, characterized in that: Calculated by mass percentage, it includes the following chemical components: Si: 1.0-1.8%, Mg: 0.8-1.2%, carbon nanotubes: 0.1-0.3%, Zr: 0.2-0.3%, the content of other inevitable impurity elements is less than 0.1%, and the balance is Al.

2. The high-strength wear-resistant aluminum-magnesium-silicon alloy according to claim 1, characterized in that: The wall thickness of the carbon nanotube is 5-10 nm.

3. The high-strength wear-resistant aluminum-magnesium-silicon alloy according to claim 1, characterized in that: The mass ratio of the carbon nanotubes to Zr is 1-3:

2.

4. The high-strength wear-resistant aluminum-magnesium-silicon alloy according to claim 1, characterized in that: The mass ratio of Si to Mg is 10-13:

8.

5. A method for preparing a high-strength wear-resistant aluminum-magnesium-silicon alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: prepare metal raw materials according to mass percentage, heat aluminum to 740-780°C to melt, raise the temperature to 1000-1500°C after it is completely melted, add zirconium and carbon nanotubes, stir and mix them for melting; Step 2: Cool down to 800-900°C, add silicon, and stir the metal solution until it is completely melted; Step 3: Cool down to 700-750°C, add magnesium, and stir until the magnesium is completely melted; Step 4: Degas and deslag the molten metal to remove oxygen, hydrogen and other harmful gases and remove slag; Step 5: Add refining agent into the molten metal for heat preservation and refining at a refining temperature of 720-740°C; Step 6: After refining, casting is carried out, and the ingot is subjected to homogenization annealing, peeling, hot extrusion forming and solution quenching treatment.

6. The method for preparing a high-strength wear-resistant aluminum-magnesium-silicon alloy according to claim 5, characterized in that: The cooling rate in step 2 is 5-10°C / min, and the cooling rate in step 3 is 3-5°C / min.

7. The method for preparing a high-strength wear-resistant aluminum-magnesium-silicon alloy according to claim 5, characterized in that: The degassing is to introduce nitrogen into the molten metal.

8. The method for preparing a high-strength wear-resistant aluminum-magnesium-silicon alloy according to claim 5, characterized in that: The refining agent is one of hexachloroethane, sodium chloride and potassium chloride, and the mass proportion of the refining agent in the molten metal is 0.05%-0.1%.

9. The method for preparing a high-strength wear-resistant aluminum-magnesium-silicon alloy according to claim 5, characterized in that: The homogenization annealing temperature is 560-600° C., and the temperature is kept for 6-8 hours before cooling to room temperature.

10. The method for preparing a high-strength wear-resistant aluminum-magnesium-silicon alloy according to claim 5, characterized in that: The solution quenching is set up as follows: The solution temperature is 540-560℃, and water quenching is carried out after keeping warm for 2-3h. The artificial aging temperature is 160-180℃, and it lasts for 8-10h.

Citation Information

Patent Citations

  • Wear-resisting aluminum alloy

    CN107974586A

Cited By

  • High-strength wear-resistant aluminum bar and preparation method thereof

    CN121006470A

  • Preparation method of hypoeutectic die-casting aluminum alloy material with high toughness and high thermal conductivity

    CN121737530A